Structurally rich dry grasslands – Potential stepping stones for bats in open farmland - Ewert, Sophie P.; Knörnschild, Mirjam; Jung, Kirsten; Frommolt, Karl-Heinz (Frontiers in Ecology and Evolution, 2023)
Agricultural intensification has caused decrease and fragmentation of European semi-natural dry grasslands. While a high biodiversity value of dry grasslands is acknowledged for plants and insects, locally and on landscape level, their relevance for mobile species, such as bats, is unknown. Here we investigate the use of dry grassland fragments by bats in an agriculturally intensified region in Germany and evaluate local and landscape factors influencing bat activity and assemblages. Specifically, we predicted that a combination of local dry grassland structural richness and landscape features as well as their interactions affect bat activity and foraging above dry grasslands. We also expected that these features influence compositions of local bat assemblages. We repeatedly sampled at 12 dry grassland plots with acoustic monitoring and assessed activity and foraging of bat species/sonotypes, which we grouped into guilds known for foraging in open land, at vegetation edges and in narrow spaces. We determined structural richness of the dry grassland plots in field and derived landscape features from digital landscape data. A relatively high proportion of bat species/sonotypes used dry grasslands regularly. The edge space foragers responded positively to higher local structural richness. Their dry grassland use increased when surrounding forests and woody features were less available, but they foraged more on dry grasslands closer to water bodies. Narrow space bat activity on dry grasslands decreased with less landscape connectivity. Open and narrow space foragers responded to local structural richness only in landscape context. For all bat guilds we found increased use of structurally richer dry grasslands when there was more open farmland in the surroundings. This was also the case for edge space foragers, when landscapes were more homogeneous. Lastly, with increasing structural richness, bat assemblages were more dominated by edge space foragers. We show the importance of European dry grassland fragments for the highly mobile group of bats under certain local structural and landscape compositional conditions. Our results underline the value of heterogeneous dry grassland fragments as potential stepping stones in intensively used farmland areas and contribute to evidence based decision making in dry grassland management and bat conservation.